Adopsi Extensible Business Reporting Language dan Asimetri Informasi - Jananti, Ni Wayan Ristiari; Wirakusuma, Made Gede; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 33 No 7 (2023)DO - 10.24843/EJA.2023.v33.i07.p01, 2023)
The research objective is to verify the effect of the adoption of Extensible Business Reporting Language (XBRL) on information asymmetry in companies listed on the IDX. The sample was selected using a purposive sampling technique which was then analyzed using multiple linear regression. The research sample consisted of 329 companies with a total sample of 1,974 companies being observed. The results of this study show that the adoption of XBRL has a positive effect on information asymmetry. Firm size and turnover ratio control variables were found to have a negative effect on information asymmetry. The research results have implications for the gap in information distribution and technology acceptance between large and small investors. XBRL can help reduce data aggregation costs, but investors must then understand how to derive the informational benefits of new data. Therefore, investors must weigh the costs of data aggregation against the benefits when deciding whether to use new technologies that are voluntary or mandatory. Keywords: Extensible Business Reporting Language; Information Asymmetry ; Bid Ask Spread.